2011
DOI: 10.1177/1538574411407087
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Endovascular Repair of Aortocaval Fistula-A Single Center Experience

Abstract: Our experience illustrates the importance of early diagnosis and management of ACF. Even in experienced hands, the management of spontaneous ACF associated with AAA is challenging. Endovascular surgery may still have a role in improving outcomes in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 16 publications
0
40
0
Order By: Relevance
“…This may have been partially because of delays in diagnosis but it also illustrates the severity and acuity of this condition. 7 This approach has the potential benefit of much less blood loss as the fistula is not repaired directly. Also, there is no need for aortic cross-clamping and the anesthetic requirements can be much less than with the open surgical approach.…”
Section: Discussionmentioning
confidence: 99%
“…This may have been partially because of delays in diagnosis but it also illustrates the severity and acuity of this condition. 7 This approach has the potential benefit of much less blood loss as the fistula is not repaired directly. Also, there is no need for aortic cross-clamping and the anesthetic requirements can be much less than with the open surgical approach.…”
Section: Discussionmentioning
confidence: 99%
“…10 A wrong or clinically missed diagnosis contributes to poor operative outcomes, especially in the typical elderly patient who may already be under hemodynamic stress. 13 Open surgery and endovascular repair are the treatment options. Supraceliac control of the aorta via an elastic loop is essential for controlling excessive bleeding, especially in an aneurysm that has a short proximal…”
Section: Discussionmentioning
confidence: 99%
“…However, one was 3 months postoperative and may have been unrelated to the surgery. 27 Furthermore, Akwei et al 38 reported 4 endovascular cases of which 3 died, but all three of those deaths had been admitted to the hospital as many as 6 days before the diagnosis of the ACF. Thus, delay in diagnosis and treatment likely played a factor in their outcome, and these patients were not likely to fare better with open surgery.…”
Section: Discussionmentioning
confidence: 99%